TEMPERATURE CALCULATION USING THERMAL BANDS OF (ETM+)SENSOR - Ghazal, Nawal; Hassoon, Khalid (Iraqi Journal of Science, 2024)
In this research, the ground temperature was calculated within a part of the provinceof Sulaymaniyah - northern Iraq, using the thermal bands(low acquisition, and highacquisition thermal bands) of the ETM+ sensor mounted in the LANDSAT 7 satellite.Practically, a linear profile within Dukan Lake (province of Sulaymaniyah) , has beenindicated, and the temperature degree for its pixel has been calculated from both lowacquisition and high acquisition thermal bands, this process has been implementedutilizing ERDAS Imagine 9.2 software package; the obtained results indicate that thereis a significant convergence between the values of temperature calculated from boththermal bands indicating the accuracy of the adopted Mathematical Model in thecalculation . In the second part of the work, the distribution of temperature degree overthe study region has been extracted as a raster map. By averaging both low gain and highgain thermal bands.